Enhancing mathematics learning outcomes through wordwall-based culturally responsive teaching - Salsabila, Dinda Nur; Ratnaningsih, Nani; Gyenin, Mary (Pasundan Journal of Mathematics Education : Jurnal Pendidikan Matematika, 2025)
This study aims to enhance students’ mathematics learning outcomes on exponent material through the use of Wordwall media integrated with the Culturally Responsive Teaching (CRT) approach at SMA Negeri 3 Tasikmalaya. The research employed a Classroom Action Research (CAR) method, conducted in two cycles with a total of 36 student participants. Data collection techniques included observation and formative assessments, using observation sheets and test instruments to evaluate both the learning process and outcomes. The findings revealed significant improvements in students’ learning outcomes following the implementation of Wordwall-based CRT learning. In the pre-cycle, the average student score was 55, with only 22.22% meeting the Learning Objective Completion Criteria (KKTP). After the first cycle, the average score increased to 77, with 70% of students meeting the KKTP. By the second cycle, the average score rose to 87, with 90% of students achieving the learning criteria. These results suggest that integrating digital interactive media with culturally responsive pedagogy can effectively improve students’ conceptual understanding and overall learning performance. Furthermore, the CRT approach contributed to increased student engagement, motivation, and active participation, creating a more inclusive and contextual learning environment that supports the diverse needs of learners in mastering the concept of exponents.